Accreditation Preparation and Implementation: A Study on Quality Assurance in Secondary Education - Muhidin, Muhidin; Julaiha, Siti (Al-Qalam Institue, 2026)
Education quality has become a critical priority in many countries as schools are increasingly required to demonstrate accountability and provide learning experiences that prepare students for future challenges. Accreditation serves as a key quality assurance mechanism to evaluate institutional performance comprehensively and transparently. This study aims to analyze the preparation and implementation processes of accreditation in secondary education institutions as an effort to improve educational quality. Using a descriptive qualitative design and a library research method, data were collected from scientific literature, government policies, and official BAN-S/M accreditation documents. The findings reveal that systematic preparation through team establishment, document management, training, and structured self-evaluation plays a decisive role in accreditation success. The study also identifies supporting factors such as leadership, teamwork, infrastructure, and community involvement, along with barriers including administrative overload, limited resources, and weak documentation systems. Theoretically, the research strengthens the framework of quality assurance by emphasizing readiness and collaboration, while practically providing guidance for policy and school improvement planning. It concludes that accreditation should function not merely as compliance but as a continuous quality development process.